Efektivitas Model Teams Games Tournament Berbantuan Game Radio-Quest terhadap Pemahaman Hasil Belajar IPAS Siswa - Putri Ayu Sekarwangi; Siti Masfuah; Yuni Ratnasari (Mataram University, 2026)
This study aimed to analyze the effectiveness of the teams games tournament (TGT) learning model assisted by the radio-quest game in improving students’ learning outcomes in IPAS. The research employed a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The participants were all 20 sixth-grade students of SD 2 Bae. Data were collected through observation, interviews, documentation, and written tests in the form of pretest and posttest. Data analysis was conducted using the Shapiro–Wilk normality test and N-Gain analysis. The results showed that the average pretest score was 65, while the average posttest score increased to 84.5. The N-Gain score obtained was 0.5707, which is categorized as a moderate improvement, while the N-Gain percentage was 57.0685, indicating that the learning model was sufficiently effective. The analysis of cognitive indicators (C1–C6) also showed a moderate increase in all aspects. These findings indicate that the application of the teams games tournament model assisted by the radio-quest game is sufficiently effective in improving the IPAS learning outcomes of sixth-grade students at SD 2 Bae.